Efficacy and safety of duloxetine versus placebo in adolescents with juvenile fibromyalgia: results from a randomized controlled trial - Himanshu P. Upadhyaya; Lesley M. Arnold; Karla Alaka; Meihua Qiao; David Williams; Renata Mehta (BMC, 2019)
Abstract Background Currently, there are no medications approved for the treatment of juvenile fibromyalgia (JFM). We evaluated the safety and efficacy of duloxetine 30/60 mg once daily (QD) versus placebo in adolescents with JFM. Methods In this Phase 3b, multisite (US, Argentina, Puerto Rico, and India) trial, patients aged 13-17 years with JFM and a score of ≥4 on the Brief Pain Inventory-Modified Short Form: Adolescent Version (BPI) 24-h average pain severity score were randomized to duloxetine or placebo for the 13-week double-blind period. The starting duloxetine dose was 30 mg, with a target dose of 60 mg QD, as tolerated. The primary endpoint was the mean change in 24-h average pain severity of the Brief Pain Inventory (BPI) from baseline to Week 13, analyzed using mixed-model repeated measures (MMRM) technique. Secondary measures were BPI severity and interference scores; treatment response (≥30%, ≥50% reductions on BPI average pain severity); Pediatric Pain Questionnaire; Clinical Global Impression of Severity: Overall and Mental Illness scales; Functional Disability Inventory: child and parent versions; Children's Depression Inventory; Multidimensional Anxiety Scale for Children; and safety and tolerability. Continuous secondary efficacy measures were analyzed using analysis of covariance or MMRM, and categorical data using Cochran-Mantel-Haenszel test and Fisher's exact test, where appropriate. Results A total of 184 patients with JFM received duloxetine (N = 91) or placebo (N = 93), of which 149 patients (81.0%) completed the 13-week double-blind treatment period. Baseline characteristics were comparable between groups; majority of the patients were Caucasian (77.17%) and females (75.0%), with a mean age of 15.53 years. For the primary measure, BPI average pain severity, the mean change was not statistically different between duloxetine and placebo (− 1.62 vs. -0.97, respectively; p = .052). For secondary efficacy outcomes, statistically significantly more duloxetine- versus placebo-treated patients had a treatment response (≥30% and ≥50% reductions on BPI average pain severity) and improvement of the general activity and relationships items on the BPI interference subscale. The percentage of patients reporting at least 1 treatment-emergent adverse event was higher in the duloxetine versus placebo groups (82.42% vs. 62.37%, respectively; p = .003). The overall safety profile of duloxetine in this study was similar to that reported previously in duloxetine pediatric trials of other indications. Conclusions The primary study outcome, mean change in 24-h BPI average pain severity rating from baseline to Week 13, did not significantly improve with duloxetine compared to placebo in patients with JFM. However, significantly more patients on duloxetine compared to placebo had a ≥30% and ≥50% reduction in pain severity. There were no new safety concerns related to duloxetine in the study population. Trial registration ClinicalTrials.gov Identifier: NCT01237587. Registered 08 November, /2010.